2017
DOI: 10.5301/jabfm.5000354
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Degradation of Polydimethylsiloxanes in Breast Implant Applications

Abstract: Material stiffening is reported as an indicator of material degradation. This altered mechanical behavior, added to the mechanical friction from tissue-tissue and tissue-implant contact and to the external mechanical loading (physical activity), may alter the material performance in women's bodies. Ultimately these changes may affect the implants' durability. Further work is needed to understand the biological aspects of the degradation process and their impact on implant durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Silk hydrogels ( Figure 4b) are easily adjustable in terms of mechanical properties and water content, so that the modification of these properties can significantly impact cell growth and function [83]. Control of the biodegradation rate of the silk hydrogel and its high bioactivity makes this biomaterial a choice for soft tissue engineering in comparison to other hydrogel-based formulations, such as polydimethylsiloxane (PDMS) and agarose [84,85], that show a negligible degradation due to the lack, in mammalian tissues, of enzymes able to decompose such materials [86,87]. A tunable degradation rate can ensure enough time for the regeneration of damaged nervous tissue.…”
Section: Silk Hydrogelsmentioning
confidence: 99%
“…Silk hydrogels ( Figure 4b) are easily adjustable in terms of mechanical properties and water content, so that the modification of these properties can significantly impact cell growth and function [83]. Control of the biodegradation rate of the silk hydrogel and its high bioactivity makes this biomaterial a choice for soft tissue engineering in comparison to other hydrogel-based formulations, such as polydimethylsiloxane (PDMS) and agarose [84,85], that show a negligible degradation due to the lack, in mammalian tissues, of enzymes able to decompose such materials [86,87]. A tunable degradation rate can ensure enough time for the regeneration of damaged nervous tissue.…”
Section: Silk Hydrogelsmentioning
confidence: 99%
“…Biomaterial degradation was studied on virgin implant shells. Stiffening was observed induced by degradation ( Martins et al, 2017 ). These phenomena, allied to tissue-tissue and tissue-implant friction and to external loads, may alter the implants’ performance and durability.…”
Section: Introductionmentioning
confidence: 99%
“…To reach our purpose, we mixed Dowsil TM SE 1700 and Sylgard 184 silicon elastomers to obtain a PDMS blend. PDMS is widely used in silicone medical devices and implants due to its non-toxic, gas permeable, and biostable properties [15][16][17][18]; PDMS also degrades very slowly in vivo [19,20]. Importantly, recent studies have shown that 3D printing of nanoparticle-free PDMS into different organ models showed enhanced cell adhesion behavior compared to non-3D-printed models [21] and that micropatterned PDMS functionalized with PLL and hyaluronic acid can minimize capsular contracture [15].…”
Section: Resultsmentioning
confidence: 99%